Entrepreneurial Intention and UAE Youth: Unique Influencers of Entrepreneurial Intentions in an Emerging Country Context. Issue 2 (3rd April 2019) - Al Saiqal, Noora Yousif; Ryan, James C.; Parcero, Osiris Jorge
Abstract: The United Arab Emirates (UAE) is a young, oil-rich country, where national youth display a clear preference for public sector employment. Growing youth unemployment reinforces the importance of non-government employment, including entrepreneurship. This study investigates UAE national youth intentions toward entrepreneurship through the Theory of Planned Behavior and the Entrepreneurial Intention Questionnaire (EIQ). Analysis ( N = 544) identifies the direct influence of attitude and perceived behavioral control and indirect influence of subjective norms on entrepreneurship intention. Results also examine several demographic variables and highlight the potential importance of family and social groups in promoting entrepreneurial intentions in this emerging country context.